2017
DOI: 10.1002/adma.201704107
|View full text |Cite
|
Sign up to set email alerts
|

Tree‐Inspired Design for High‐Efficiency Water Extraction

Abstract: The solar steam process, akin to the natural water cycle, is considered to be an attractive approach to address water scarcity issues globally. However, water extraction from groundwater, for example, has not been demonstrated using these existing technologies. Additionally, there are major unaddressed challenges in extracting potable water from seawater including salt accumulation and long-term evaporation stability, which warrant further investigation. Herein, a high-performance solar steam device composed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
391
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 560 publications
(398 citation statements)
references
References 34 publications
5
391
1
1
Order By: Relevance
“…[6,[16][17][18][19][20] However, water is a thermally conductive material with high thermal conductivity of 0.599 W K −1 m −1 , much higher than the commonly used thermal-insulating materials (e.g., 0.117 W K −1 m −1 of carbon foam, [6] 0.069 W K −1 m −1 of bacteria nanocellulose, [16] and 0.016 W K −1 m −1 of graphene foam [19] ). [6,[16][17][18][19][20] However, water is a thermally conductive material with high thermal conductivity of 0.599 W K −1 m −1 , much higher than the commonly used thermal-insulating materials (e.g., 0.117 W K −1 m −1 of carbon foam, [6] 0.069 W K −1 m −1 of bacteria nanocellulose, [16] and 0.016 W K −1 m −1 of graphene foam [19] ).…”
Section: Introductionmentioning
confidence: 99%
“…[6,[16][17][18][19][20] However, water is a thermally conductive material with high thermal conductivity of 0.599 W K −1 m −1 , much higher than the commonly used thermal-insulating materials (e.g., 0.117 W K −1 m −1 of carbon foam, [6] 0.069 W K −1 m −1 of bacteria nanocellulose, [16] and 0.016 W K −1 m −1 of graphene foam [19] ). [6,[16][17][18][19][20] However, water is a thermally conductive material with high thermal conductivity of 0.599 W K −1 m −1 , much higher than the commonly used thermal-insulating materials (e.g., 0.117 W K −1 m −1 of carbon foam, [6] 0.069 W K −1 m −1 of bacteria nanocellulose, [16] and 0.016 W K −1 m −1 of graphene foam [19] ).…”
Section: Introductionmentioning
confidence: 99%
“…This sophisticated structure has important effects on wood properties, especially related to moisture control, strength‐to‐weight ratio, and anisotropy. Moreover, recent studies have shown that wood's structural features are useful for a wide range of potential applications, such as mechanically stable scaffolds for stimuli‐responsive hydrogels, natural templates for nanoparticle assembly, wood membranes for water treatment, and water extraction . However, its hierarchical structure is underused in most wood‐based materials and, therefore, its beneficial properties cannot be fully leveraged …”
Section: Introductionmentioning
confidence: 99%
“…The preparation process and cost of solar evaporators can therefore be greatly simplified and reduced, which is of great significance to future large-scale applications. [27,30] Hydrophilicity is widely accepted as a desirable characteristic for solar evaporators because water at the base can be delivered promptly up to the top hot region, making evaporation efficient and sustainable. The highly rich mesostructure of balsa wood contributes to its super low density and good mechanical performance.…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40] However, in-depth understanding of evaporator-seawater interaction is not yet revealed systematically. [30,41] Soaking in waters with different salinity, specific weight of the wood block increased over time, but unlike the control experiment with pure water, salinity unaccountably retarded water uptake (Figure 5a).…”
Section: Wwwadvsustainsyscommentioning
confidence: 88%